Minimally Invasive Treatment of Mirizzi Syndrome, a Rare Cause of Cholestasis in Childhood - Ahmet Ali Tuncer; Sezgin Yilmaz; Mustafa Yavuz; Salih Çetinkurşun (Hindawi Limited, 2016)
Mirizzi syndrome is the compressive blockage of the cystic or choledochal duct caused by a biliary stone occupying the cystic canal or Hartmann's pouch. This occurrence is rare and, in English literature, three cases defined in children have been observed. In order to draw attention to this rare occurrence, we preferred a 14-year-old male patient with Mirizzi syndrome. In this case, ERCP was performed preoperatively and the diagnosis was carried out with the help of clear visualisation and identification of the tissue structures as well as the stent placed in bile duct; so we protected the patient from the possible iatrogenic injury occurring during surgery.